(untitled) (Revista Sistemas de Producción Agroecológicos, 2012)
The hydroponic green fodder (HGF) is a variant of hydroponics; process of rapid germination of viable seeds of some cereals held in adequate facilities for that purpose and under controlled processes, for a period of time no longer than 12 days, 9 of which is supplied to seedlings nutrient solutions, which occurs at the end of the cycle consists of a mat sprouted grains, with their roots, stems and green leaves plant biomass thus obtained is of high health and nutritional quality. Is thus an interesting possibility to supply efficiently diets of ruminants and non-ruminants. It aims to socialize, data, experiences and results obtained on HGF produced in Colombia, with the hope that this would constitute a useful tool for those interested in implementing this technology. To develop the project objectives, vegetative material was obtained at 4, 6, 8, 10, 12 and 14 days of harvest, which will take a random sample and chemical composition analysis was conducted in the laboratory of animal nutrition at the University of the Plains, which sought to establish the behavior of HGF protein versus time of harvest. The HGF of Zea maize shows a peak of protein on the tenth day after which begins to decline slightly to twelve days thereafter presents a precipitous decline. The maximum germination of seedlings the day should not exceed twelve.